1995
DOI: 10.1093/jnci/87.22.1705
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Association of Human Papillomavirus With High-Grade Histologic Variants of Penile-Invasive Squamous Cell Carcinoma

Abstract: The presence of HPV DNA was found to be significantly associated only with those penile SCC exhibiting basaloid changes. Furthermore, HPV DNA sequences tended to be associated with higher grade and more aggressive tumor localized to the glans penis. The low frequency of HPV in penile SCC implies that only a small proportion of these cancers arise from HPV-associated penile SIL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
121
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(137 citation statements)
references
References 0 publications
12
121
0
4
Order By: Relevance
“…It is necessary to search for non--invasive biomarkers with good accuracy, to predict the risk of metastatic lymph node involvement in patients with penile cancer (22,23). In our series, there was no association between the presence or distribution of HPV genotype with lymph node disease, as reported by other authors (13,19). At present, there are no evidences indicating the use of HPV detection in order to decide to perform lymphadenectomies.…”
Section: Discussionsupporting
confidence: 45%
“…It is necessary to search for non--invasive biomarkers with good accuracy, to predict the risk of metastatic lymph node involvement in patients with penile cancer (22,23). In our series, there was no association between the presence or distribution of HPV genotype with lymph node disease, as reported by other authors (13,19). At present, there are no evidences indicating the use of HPV detection in order to decide to perform lymphadenectomies.…”
Section: Discussionsupporting
confidence: 45%
“…16 Gregoire et al observed that HPV DNA was detected significantly more often in penile carcinomas exhibiting a more vertical growth pattern and in histologically defined high-grade tumors. 27 The current analysis suggests a survival benefit for penile cancer patients in whom high-risk HPV DNA was present in the primary tumor compared with patients in whom no high-risk HPV DNA could be detected. Although historical control analysis is not ideal to compare survival, because of potential time-related changes in various characteristics, the benefit could not be explained by differences in patient or primary tumor histopathological characteristics.…”
Section: Discussionmentioning
confidence: 76%
“…8,10 The reported frequency of penile verrucous carcinoma is low and accounts for 3-20% of all penile cancers. 5,6,[11][12][13] However, identification of cases from the literature is sometimes difficult because of the varied nomenclature used in the past, often regarding them as the same lesion as BLT. 14,15 Risk factors for penile verrucous carcinoma seem to be similar as for penile cancer in general, which are poor hygiene, phimosis and chronic inflammation 16 but no systematic case series has been studied.…”
mentioning
confidence: 99%